Clinical impact of conduction disturbances in transcatheter aortic valve replacement recipients: a systematic review and meta-analysis. (3rd January 2020) - Faroux, Laurent; Chen, Shmuel; Muntané-Carol, Guillem; Regueiro, Ander; Philippon, Francois; Sondergaard, Lars; Jørgensen, Troels H; Lopez-Aguilera, José; Kodali, Susheel; Leon, Martin; Nazif, Tamim; Rodés-Cabau, Josep
Abstract: Aims: The clinical impact of new-onset persistent left bundle branch block (NOP-LBBB) and permanent pacemaker implantation (PPI) on transcatheter aortic valve replacement (TAVR) recipients remains controversial. We aimed to evaluate the impact of (i) periprocedural NOP-LBBB and PPI post-TAVR on 1-year all-cause death, cardiac death, and heart failure hospitalization and (ii) NOP-LBBB on the need for PPI at 1-year follow-up. Methods and results: We performed a systematic search from PubMed and EMBASE databases for studies reporting raw data on 1-year clinical impact of NOP-LBBB or periprocedural PPI post-TAVR. Data from 30 studies, including 7792 patients (12 studies) and 42 927 patients (21 studies) for the evaluation of the impact of NOP-LBBB and PPI after TAVR were sourced, respectively. NOP-LBBB was associated with an increased risk of all-cause death [risk ratio (RR) 1.32, 95% confidence interval (CI) 1.17–1.49; P < 0.001], cardiac death (RR 1.46, 95% CI 1.20–1.78; P < 0.001), heart failure hospitalization (RR 1.35, 95% CI 1.05–1.72; P = 0.02), and PPI (RR 1.89, 95% CI 1.58–2.27; P < 0.001) at 1-year follow-up. Periprocedural PPI after TAVR was associated with a higher risk of all-cause death (RR 1.17, 95% CI 1.11–1.25; P < 0.001) and heart failure hospitalization (RR 1.18, 95% CI 1.03–1.36; P = 0.02). Permanent pacemaker implantation was not associated with an increased risk of cardiac death (RR 0.84, 95% CI 0.67–1.05; P = 0.13). Conclusion: NOP-LBBB and PPI after TAVR are associated with an increased risk of all-cause death and heart failure hospitalization at 1-year follow-up. Periprocedural NOP-LBBB also increased the risk of cardiac death and PPI within the year following the procedure. Further studies are urgently warranted to enhance preventive measures and optimize the management of conduction disturbances post-TAVR.